Glial Adenosine Kinase – a Neuropathological Marker of the Epileptic Brain - Aronica, Eleonora (2013)
Experimental research over the past decade has supported the critical role of astrocytes activated by different types of injury and the pathophysiological processes that underlie the development of epilepsy. In both experimental and human epileptic tissues astrocytes undergo complex changes in their physiological properties, which can alter glio-neuronal communication, contributing to seizure precipitation and recurrence. In this context, understanding which of the molecular mechanisms are crucially involved in the regulation of glio-neuronal interactions under pathological conditions associated with seizure development is important to get more insight into the role of astrocytes in epilepsy. This article reviews current knowledge regarding the role of glial adenosine kinase as a neuropathological marker of the epileptic brain. Both experimental findings in clinically relevant models, as well as observations in drug-resistant human epilepsies will be discussed, highlighting the link between astrogliosis, dysfunction of adenosine homeostasis and seizure generation and therefore suggesting new strategies for targeting astrocyte-mediated epileptogenesis.